Dialektika Eksistensial Cinta dalam Kumpulan Puisi Sepotong Hati di Angkringan Karya Joko Pinurbo - Lestari, Arsys Nabella Dwi; Suminto, Suminto; Efendi, Anwar (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
The COVID-19 pandemic triggered an existential crisis that compelled individuals to rediscover spiritual and emotional foundations through the reinterpretation of love in literary works. This study examines the existential meaning of love in Joko Pinurbo's poetry collection Sepotong Hati di Angkringan, integrating two complementary theoretical frameworks: Erich Fromm's five objects of love in humanistic psychology (brotherly, maternal, erotic, self-love, and love of God) and Paul Ricoeur's three-stage hermeneutics (semantic, reflective, and ontological). This research employs a qualitative method based on library research with a hermeneutic content analysis design applied to seven purposively selected poems. At the semantic stage, the five objects of love were identified through lexical ambiguity and domestic imagery such as the clinking of a spoon, a drying sarong, and the ritual of bathing. At the reflective stage, these signs were connected to the psychological reality of isolated individuals during the pandemic, revealing love as an active response to existential alienation. At the ontological stage, love was found to operate as a way of being that transcends physical presence and temporal boundaries. The analysis demonstrates that Fromm's five objects of love do not operate in isolation but interpenetrate to form a unified existential survival mechanism. This study concludes that Jokpin's poetry functions as an existential refuge that transforms love from mere sentiment into a fundamental life force in the midst of crisis.